A phase 2, open label, multicenter, single arm study of tocilizumab on the efficacy and tolerability of tocilizumab in the treatment of patients with COVID-19 pneumonia (TOCIVID-19 trial): Statistical analysis plan - Paolo Chiodini; Laura Arenare; Maria Carmela Piccirillo; Francesco Perrone; Ciro Gallo (Contemporary Clinical Trials Communications, 2020)
Background: Tocilizumab, an IL-6 receptor antagonist, was suggested as a possible treatment of severe or critical COVID-19 pneumonia in a small Chinese study. The TOCIVID-19 trial evaluates efficacy and tolerability of tocilizumab in the treatment of patients with severe or critical COVID-19 pneumonia. Methods: TOCIVID-19 is an academic multicenter, single-arm, open-label, phase 2 study. All the patients are being offered a single shot of 8 mg/kg of Tocilizumab (up to a maximum of 800 mg), with an eventual second administration at the discretion of the Investigator. A companion prospective cohort, added to corroborate internal validity, includes either patients not eligible for phase 2 or subjects eligible for phase 2 but exceeding the planned sample size. 14- and 30-days lethality rates are the two co-primary endpoints in the intention-to-treat (ITT) population. Secondary objectives are to evaluate mortality and clinical improvement in the modified-ITT population of subjects who received the drug. Details of the methodological and statistical approaches are reported here reflecting the amendments impelled by the continuously increasing knowledge on COVID-19 progression and challenges in data collection. Conclusion: This paper provides details of planned statistical analyses for TOCIVID19 trial to reduce the risk of reporting bias and increase validity of the study findings.TOCIVID-19 trial is registered in the EudraCT database with number 2020-001110-38 and in clinicaltrials.gov with ID NCT04317092.